Modern aspects of tactics in the genital herpes viral infection (literature review) - T Yu Pestrikova; E A Yurasova; I V Yurasov; A V Kotelnikova (IP Berlin A.V., 2018)
Genital herpes affects all population groups. 98% of the adult population worldwide have antibodies to the herpes simplex virus (HSV-1 or 2). This viral infection is a significant medical and social problem. HSV can lead to a complicated course of pregnancy, causing miscarriages, premature birth, intrauterine fetal death, systemic viral disease in newborns. There is evidence that HSV has a connection with malignant tumors of the prostate and cervix, contributing to their development. This literature review contains modern aspects of epidemiology, etiology, pathogenesis, clinic, diagnosis, treatment of genital herpes, including its recurring forms with valacyclovir (Valvir). Indications for hospitalization of patients with genital herpes were noted and the prognosis of this pathology was determined. The tactics of managing pregnant women with this pathology is presented.